Santri dan Inovasi Wirausaha: Sebuah Tinjauan Sistematis - Nur Alfia; Moh. Zamili (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2024)
This research aims to examine the existence and innovation of Islamic boarding school students in Indonesia in the entrepreneurial arena over the last 10 years. The study used a systematic literature review to pay attention to trends in business types, entrepreneurial innovation practices in Islamic boarding schools, and the entrepreneurial spirit based on Islamic values. Literature sources were obtained from databases on Garuda (Gr), and Google Scholar (GS). The research results in 35 literature GS, 20 literature dari Gr, show no match between the interests and types of business taught in the training and the experiences shared by the trainers. Innovative practices regarding Islamic boarding school entrepreneurship are not entirely based on the latest technology, ignore customer satisfaction and persuasive communication regarding Islamic boarding school products is limited to alumni. Meanwhile, the entrepreneurial spirit has not yet synergized between practice and theory, especially Islamic values.